Does Sacrococcygeal Skeletal Morphology and Morphometry Influence Pressure Injury Formation in Adults?. (November 2022) - Delmore, Barbara; Sprigle, Stephen; Samim, Mohammad; Alfonso, Allyson R.; Lin, Lawrence; Chiu, Ernest
Abstract : GENERAL PURPOSE: To present a study that investigated sacrococcygeal skeletal structure as a possible nonmodifiable intrinsic risk factor for pressure injury and identify possible issues caused by its morphology. TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Recognize the background information the authors considered when planning and conducting their study of sacrococcygeal skeletal structure as a possible pressure injury risk factor. 2. Identify the characteristics of the two groups of study participants. 3. Choose the results of the study clinicians may consider when implementing evidence-based practice. ABSTRACT: Objective: To determine if sacrococcygeal skeletal morphology and morphometry characteristics were possible pressure injury (PI) intrinsic risk factors; determine the exact location of these PIs; and generate hypotheses and determine methodological considerations required for future larger studies. Methods: This case-control pilot study compared 30 patients who had an MRI scan—15 patients had a PI and 15 patients did not. Key sacrococcygeal morphology and morphometry parameters were assessed. Results: On average, patients with PIs had less of a lumbosacral and sacrococcygeal angle and a greater sacral curvature and intercoccygeal angle than did patients without a PI. Patients with PIs had more variable coccyx types. Tissue and bone destruction precluded several measurements in some patients. The most common area of destruction was located distally. Conclusion: Sacrococcygeal measurements differed in patients with PIs, and PIs were predominately located distally. Authors recommend replicating this study on a larger scale because certain key attributes warrant further investigation to determine their influence on sacrococcygeal PIs. Sacrococcygeal morphology and morphometry parameters have not been previously studied as possible intrinsic risk factors for PIs; yet, this is the most common location for their occurrence. Knowledge regarding possible injury mechanisms due to the forces from overlying skeletal structures with respective tissue loading over the sacrococcygeal area has the potential to inform practice; preventive strategies; and equipment, products, and technology developed.